2011
DOI: 10.1038/ismej.2011.171
|View full text |Cite
|
Sign up to set email alerts
|

Denitrification likely catalyzed by endobionts in an allogromiid foraminifer

Abstract: Nitrogen can be a limiting macronutrient for carbon uptake by the marine biosphere. The process of denitrification (conversion of nitrate to gaseous compounds, including N 2 (nitrogen gas)) removes bioavailable nitrogen, particularly in marine sediments, making it a key factor in the marine nitrogen budget. Benthic foraminifera reportedly perform complete denitrification, a process previously considered nearly exclusively performed by bacteria and archaea. If the ability to denitrify is widespread among these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
82
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(82 citation statements)
references
References 48 publications
(60 reference statements)
0
82
0
Order By: Relevance
“…This surprising ability to accumulate nitrate and its respiration to dinitrogen gas was later confirmed in benthic foraminifera in OMZ sediments off the Chilean coast (Hogslund et al, 2008) and demonstrated in laboratory experiments (Pina-Ochoa et al, 2010). However, in at least one species, symbiotic bacteria appear to be responsible for respiring the nitrate, not the foraminifera (Bernhard et al, 2012). Since most other eukaryotic organisms, especially macrofauna, are not as tolerant to hypoxia as foraminifera (Josefson and Widbom, 1988), they often are absent from sediments in the core of the OMZ ).…”
mentioning
confidence: 79%
“…This surprising ability to accumulate nitrate and its respiration to dinitrogen gas was later confirmed in benthic foraminifera in OMZ sediments off the Chilean coast (Hogslund et al, 2008) and demonstrated in laboratory experiments (Pina-Ochoa et al, 2010). However, in at least one species, symbiotic bacteria appear to be responsible for respiring the nitrate, not the foraminifera (Bernhard et al, 2012). Since most other eukaryotic organisms, especially macrofauna, are not as tolerant to hypoxia as foraminifera (Josefson and Widbom, 1988), they often are absent from sediments in the core of the OMZ ).…”
mentioning
confidence: 79%
“…2 and 3). If deeply infaunal foraminifera do not migrate, they likely rely on anaerobic metabolism, such as denitrification, which is documented in a considerable variety of foraminifera and/or their symbionts (25,26). It is not known at this time if any of the Highborne Cay microbialite foraminifera perform complete denitrification.…”
Section: Discussionmentioning
confidence: 99%
“…(phylotype 6 and phylotype unknown) may be a host to various species of intracellular bacteria, and that the bacterial assemblages comprising the foraminiferal microbiome may change in time and space. Various endobionts have been described for other foraminiferal species that inhabit anoxic sediments (e.g., Bernhard, 2003;Bernhard et al, 2012;Tsuchiya et al, 2015;Bernhard et al, 2017). Therefore, the presence of bacterial endobionts in foraminifera coming from anoxic sediments seems relatively widespread.…”
Section: Potential Bacterial Endosymbionts In the Foraminiferal Cytosmentioning
confidence: 99%
“…Anaerobic metabolism, namely denitrification via an intracellular nitrate pool, has been demonstrated for various species of benthic foraminifera (Risgaard-Petersen et al, 2006;Piña-Ochoa et al, 2010;Bernhard et al, 2012). However, it is currently not known whether denitrification is catalyzed by the foraminifera proper, or by potential endosymbionts of the foraminifera; evidence for both strategies exists (Risgaard-Petersen et al, 2006;Bernhard et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation